2014
DOI: 10.1542/peds.2014-0140
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Benefit Analysis of a Medical Emergency Team in a Children’s Hospital

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Numerous studies have demonstrated clinical benefits of medical emergency team (MET) implementation, including reductions in mortality, cardiac arrests, and critical deterioration events. No studies have evaluated the financial costs and benefits of METs. WHAT THIS STUDY ADDS:The costs of operating an MET can plausibly be recouped with a modest reduction in critical deterioration events. Hospitals reimbursed with bundled payments could see real financial savings by reducing critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 22 publications
2
36
0
1
Order By: Relevance
“…This amounts to 0.77 children receiving CPR per 1000 hospital admissions [6]. Due in part to the widespread implementation of rapid response systems in most children's hospitals [8][9][10] and the recognition of at-risk in-patients, >95% of CPR events in the USA occur in ICUs [11]. The prevalence of CPR among one cohort of academic children's hospitals was 1.4% from 2010 to 2013, compared with 1.8% reported in the 1990s [7].…”
Section: Epidemiology Of Pediatric In-hospital Cardiac Arrestmentioning
confidence: 99%
“…This amounts to 0.77 children receiving CPR per 1000 hospital admissions [6]. Due in part to the widespread implementation of rapid response systems in most children's hospitals [8][9][10] and the recognition of at-risk in-patients, >95% of CPR events in the USA occur in ICUs [11]. The prevalence of CPR among one cohort of academic children's hospitals was 1.4% from 2010 to 2013, compared with 1.8% reported in the 1990s [7].…”
Section: Epidemiology Of Pediatric In-hospital Cardiac Arrestmentioning
confidence: 99%
“…This is apparent in that most studies demonstrated trends of improving cardiac arrest rate or mortality, although not to statistically significant levels. Use of a more proximate outcome metric, like a critical deterioration event, 25 might further support implementation of a MET/RRT in the pediatric inpatient setting.…”
Section: Knowledge Gapsmentioning
confidence: 99%
“…Otherwise, adverse events may occur in ICU patients while critical care staff are on RRT calls [13]. Importantly, cost savings associated with preventing unplanned ICU admissions may in itself justify the funding of a hospital-wide RRS [14].…”
Section: Resource Considerationsmentioning
confidence: 99%